2013
DOI: 10.1186/1476-069x-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Environmental footprints of Mediterranean versus Western dietary patterns: beyond the health benefits of the Mediterranean diet

Abstract: BackgroundDietary patterns can substantially vary the resource consumption and environmental impact of a given population. Dietary changes such as the increased consumption of vegetables and reduced consumption of animal products reduce the environmental footprint and thus the use of natural resources. The adherence of a given population to the Mediterranean Dietary Pattern (MDP) through the consumption of the food proportions and composition defined in the new Mediterranean Diet pyramid can thus not only infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
207
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(224 citation statements)
references
References 24 publications
12
207
1
4
Order By: Relevance
“…This is because it is mainly a plant-based diet with low consumption of animal products and thus has a smaller water footprint and lower greenhouse gas emissions, compared with other current dietary patterns (25)(26)(27)(28)(29) . Increased adherence of the Spanish population to the MDP was reported to have a marked impact on all standard environmental footprints: reduce greenhouse gas emissions, land use and energy consumption, and to a lower extent water consumption, while on the contrary, adherence to a Western dietary pattern increases all these parameters (81) . In an Italian study, adherence to the MDP was shown to significantly reduce the food environmental footprint on natural resources especially for water consumption (82) .…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…This is because it is mainly a plant-based diet with low consumption of animal products and thus has a smaller water footprint and lower greenhouse gas emissions, compared with other current dietary patterns (25)(26)(27)(28)(29) . Increased adherence of the Spanish population to the MDP was reported to have a marked impact on all standard environmental footprints: reduce greenhouse gas emissions, land use and energy consumption, and to a lower extent water consumption, while on the contrary, adherence to a Western dietary pattern increases all these parameters (81) . In an Italian study, adherence to the MDP was shown to significantly reduce the food environmental footprint on natural resources especially for water consumption (82) .…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…One diet pattern that is considered useful for the prevention/ improvement of intestinal diseases is the Mediterranean diet. This is characterized by a high intake of fruit and vegetables (rich in fiber, antioxidants and vitamins), olive oil and oily fish (rich in mono and polyunsaturated fatty acids), and whole grains and nuts 15,24 . It is based on the daily or weekly consumption of specific food groups according to the standardized food pyramid 24 .…”
Section: How Nutrition and Diet Can Influence Microbiota And Correct mentioning
confidence: 99%
“…This is characterized by a high intake of fruit and vegetables (rich in fiber, antioxidants and vitamins), olive oil and oily fish (rich in mono and polyunsaturated fatty acids), and whole grains and nuts 15,24 . It is based on the daily or weekly consumption of specific food groups according to the standardized food pyramid 24 . Current research on probiotics, as a food supplement in addition to a mediterranean diet, showed that probiotics (such as Lactobacillus Rhamnosus) changes the composition of the microbiota, thus allowing the return to eubiosis 5 .…”
Section: How Nutrition and Diet Can Influence Microbiota And Correct mentioning
confidence: 99%
“…The methodology used in this paper for the calculation of the water footprint of national food supply is similar to that used by [51] in their analysis of the environmental footprint of the Spanish dietary pattern. Water footprints of crops and derived crop products as well as farm animals and animal products were obtained from the main report of Mekonnen and Hoekstra [22,52].…”
Section: Methodsmentioning
confidence: 99%